Subcutaneous Panniculitis-Like T-Cell Lymphoma Presenting as a Local Inflammation of a Thigh in an 8-Month-Old Child - Gizewska-Kacprzak, Kaja; Karpinska-Kaczmarczyk, Katarzyna; Ociepa, Tomasz (European Journal of Pediatric Surgery Reports, 2017)
During infancy, skin inflammation is usually treated in basic pediatric care. In this study, we present a case of an 8-month-old girl with a 2-month history of an inflammation of the thigh treated locally by ointments and oral antibiotics in basic and dermatological care. The patient had a history of fever, sweating, and failure to thrive. The lactate dehydrogenase was elevated up to 869 U/L with low C-reactive protein (1.04 mg/L). Magnetic resonance imaging of the thigh reassured the diagnosis of local inflammation. Intravenous antibiotic caused mild local improvement, but the episodes of high fever sustained. The patient was transferred to our pediatric surgery department for treatment and surgical biopsy of the lesion. Histopathological examination confirmed a subcutaneous panniculitis-like T-cell lymphoma, which is a rare cytotoxic T-cell lymphoma representing less than 1% of non-Hodgkin lymphomas, uncommon in children. The patient was introduced to a chemotherapy protocol EURO-LB 2002 with good response. In a skin lesion that is associated with systemic symptoms and responding untypically to antibiotic treatment malignancy should be considered and biopsy not be postponed.
Keywords: cutaneous T-cell lymphoma; child; subcutaneous panniculitis-like T-cell lymphoma; immunohistochemistry